Development of an early detection method white root disease of rubber: A preliminary investigation - Fernando THPS; Jayasinghe CK; Siriwardene D (Journal of the Rubber Reaserch Institute of Sri Lanka, 2011)
White root disease is the most destructive root disease of rubber in Sri Lanka and the rubber growers are confronted with the problem of early detection of this disease. The present study was aimed at investigating the possible early detection techniques to increase the effectiveness of chemical control programmes. The artificial inoculation of the plants was faster with naturally infected root inocula than the artificially prepared inocula. Fourteen weeks after mulching, all the plants under investigation showed rhizomorph on the collar region. The rapid upward movement of the fungus in the presence of a mulch is shown to be useful for early detection of the white root disease.
Keywords: Early detection; Mulching; White root disease